1966
DOI: 10.1021/ic50037a014
|View full text |Cite
|
Sign up to set email alerts
|

The Infrared Spectra of Rare Earth Metal Chloride Complexes of 2,2'-Bipyridyl and 1,10-Phenanthroline from 650 to 70 Cm-11

Abstract: The infrared spectra of rare earth metal chloride complexes of 2,2'-bipyridyl and 1,lO-phenanthroline are reported from 650 to 70 cm-'. The position of the V M -N vibration is observed to vary with the properties of the metal and ligand.From the infrared spectra in this region, frequency assignments are suggested for the Y M -N vibrations.A number of 2-carbamoyldimedone and N-phenyl-2-carbamoyldimedone complexes of the first transition metal series have been synthesized. The metal-ligand coordination has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1968
1968
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The medium intensity band at 620 cm-I moves 15-25 cm-I to higher frequency on complexing and the 403 cm-I band is resolved into two or three components in the complexes. Similar changes have been noted previously (5,18,19). A strong band at 560 cm-' with shoulders at 540 and 546 cm-I is presumably v4(t1,) of PF,-in [GaX,(bipy),]-PF, and v4(t2) of BF,-in [GaCl,(bipy),]BF, is at 541 cm-I.…”
Section: Infrared Spectrasupporting
confidence: 85%
“…The medium intensity band at 620 cm-I moves 15-25 cm-I to higher frequency on complexing and the 403 cm-I band is resolved into two or three components in the complexes. Similar changes have been noted previously (5,18,19). A strong band at 560 cm-' with shoulders at 540 and 546 cm-I is presumably v4(t1,) of PF,-in [GaX,(bipy),]-PF, and v4(t2) of BF,-in [GaCl,(bipy),]BF, is at 541 cm-I.…”
Section: Infrared Spectrasupporting
confidence: 85%
“…30 (2) It has also been reported that water molecules bound to Fe give broad bands (ν 1/2 ) ca. 430 cm -1 ) around 3400 cm -1 , 31 and that bridging OH groups between metal ions of Fe, Cu, and Co give broad bands from 3300 to 3600 cm -1 , [32][33][34] as observed for TBA-I.…”
Section: Resultsmentioning
confidence: 69%
“…In reactions 1 and 2 only the first four terms of eq 5 contribute to the rate expression while in reaction 3 all five terms contribute to the expression. The second (&LCuTr) and third (&HLCuTr) terms in eq 6 can alternatively be expressed as the mono-and diprotonated ligand attack on Cu (OH) tren since the regres- (11) Stability constants for the different complexes at 25°and 0.1 M ionic strength: CuTr, log K -18.8; CuT, log K = 20.1; CuTe, log K = 22.9; CuD, log K = 15.8; CuD2, log K = 5.22; Cu(OH)Tr, log Ki = 4.65. See L. G. Sillén and A. E. Martell, Ckem.…”
Section: Resultsmentioning
confidence: 99%